Gene editing with CRISPR-Cas12a guides possessing ribose-modified pseudoknot handles - Eman A. Ageely (Nature Portfolio, 2021)
Development of Cas12a for human therapeutics and diagnostics may significantly benefit from, or even require, chemical modification of its guide RNA. Here the authors show that the noncanonical 5′ pseudoknot structure of the AsCas12a crRNA guide can be heavily modified and still retain very high editing activity in cells and trans cleavage activity in vitro.